Steady-State Properties of Driven Polydisperse Granular Mixtures - 李睿 张端明 肖明 李志浩 (Communications in theoretical physics, 2011)
We represent a two-dimensional model of polydisperse granular mixtures with a power-law size distribution. The model consists of smooth hard disks in a rectangular box with inelastic collisions, driven by a homogeneous heat bath at zero gravity. The width of particle size distribution is characterized by the only parameter, namely, the fractal dimension D. The energy dissipation of the mixture is increased as D increases or as e decreases. Furthermore, it is found that the steady-state properties of the mixture such as the collision rate, granular temperature, kinetic pressure and velocity distribution depend sensitively on size distribution parameter D.